Evaluation of Noise Pollution in Bengaluru City, India During COVID-19 Pandemic - ANJUM, Saima; KUMARI, Anupma (Archives of Acoustics, 2022)
Most of the Indian cities and towns have been facing serious traffic noise pollution due to urbanization, substantial growth of new vehicles, inadequate road network, etc. Automotive traffic, railroads, and air traffic are the most common sources of noise pollution in cities, with vehicular traffic accounting for around 55% of overall metropolitan noise. Prolonged exposure to such loud noise causes anger, stress, mental diseases, discomfort, hypertension, concentration problems, and sleeplessness. This study aims to investigate the effects of COVID-19 societal lockdown on changes in the noise pollution levels before, during, and after the lockdown period in various industrial, commercial, residential, and silence zones in Bengaluru, India, in light of the recent imposition of COVID-19 societal lockdown. According to data acquired from the KSPCB (Karnataka State Pollution Control Board) online portal, the average noise levels before and during lockdown were determined to be in the range of 59.4 dB to 70.9 dB and 58.2 dB to 62.7 dB for different zones. During the lockdown, all commercial, industrial and educational activities were closed to limit the spread of infection, resulting in usage of private and commercial transportation declining dramatically. Reduction in the noise level was observed during the lockdown in all monitoring stations of Bengaluru, except for Indira Gandhi Institute of Child Health, where the noise level didn’t decline because of a COVID emergency. Maximum reduction was observed in the commercial area (11.56%) followed by industrial areas (8.34%). The result further indicated that only the industrial area experienced an increase of 8.41% in noise level, while other areas experienced a reduction in a noise level during the early post-lockdown. During the mid and late post-lockdown periods, most locations experienced a rapid spike in the noise intensity.